Frank Norrisâs Portrayal of Naturalism in âMcTeagueâ (An Analysis of American Literary Naturalism in the Late Nineteenth-Century) - , NURFANI, S.S.; , Prof. Dr. C. Soebakdi Soemanto, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis observes âFrank Norrisâs Portrayal of Naturalism in McTeague. The analysis is based on 3 things as fundamental knowledge in doing research